Understanding and addressing factors affecting carers’ mental health during end-of-life caregiving: synopsis of meta synthesis of literature and stakeholder collaboration - Gunn Grande; Christine Rowland; Tracey Shield; Kerin Bayliss; Jackie Flynn; Danielle Harris; Alison Wearden; Morag Farquhar; Maria Panagioti; Alexander Hodkinson; Margaret Booth; David Cotterill; et al. (Health and Social Care Delivery Research)
Background Family carers provide crucial support to patients nearing end of life. This can affect carers’ own mental health negatively. It is important to understand what factors may affect carers’ mental health and convey this information to stakeholders who can effect change. We conducted reviews of the qualitative, observational and intervention carer literature and worked with carer advisors and other stakeholders to make findings useful and accessible. Aim of the synopsis To provide a synopsis of (1) project methods, (2) findings and implications from the evidence syntheses, (3) outcomes of our carer Review Advisory Panel collaboration and (4) feedback from wider stakeholder consultation. Method Searches of MEDLINE, Cumulative Index to Nursing and Allied Health Literature, PsycInfo, Social Sciences Citation Index, EMBASE, Cochrane Central Register of Controlled Trials and Database of Abstracts of Reviews of Effects 1 January 2009–24 November 2019. Studies included adult family carers for adult patients at the end of life cared for at home, considering any factor related to carer mental health. Collaboration with the Review Advisory Panel over nine meetings helped map review findings into a framework, shape their presentation and create Review Advisory Panel recommendations. Four workshops, two discussion groups and a survey with stakeholders (carers/patients, practitioners and policy-makers/commissioners) informed output formats and suggested actions. Results Thirty-one qualitative, 60 observational, 12 intervention and 3 mixed-methods studies were identified. Factors associated with carer mental health were: (1) patient condition, mainly psychological symptoms and quality of life; (2) impact of caring responsibilities, mainly life changes, workload and carer burden; (3) relationships, particularly carer–patient; (4) finances, whether sufficient; (5) internal processes, particularly self-efficacy; (6) support, particularly adequacy and quality; and (7) contextual factors, mainly age and gender. The Review Advisory Panel comprised five carers and a carer chair. They created recommendations for supporting carers based on syntheses findings, including: awareness raising for carers and practitioners; a road map to help carers navigate caregiving; bespoke carer support through carer assessment; assessment of patient’s actual rather than ‘managed’ needs; co-ordinated care through a single contact point; addressing basic practical needs. Other key recommendations included holistic, co-ordinated patient care and cover of basic carer financial needs. Thirty-six stakeholders participated in workshops and discussion groups and 43 in the survey, to review synthesis findings and Review Advisory Panel recommendations. Stakeholders generally valued the qualitative evidence and recommendations over the quantitative evidence, although all outputs resonated with them. There was little consensus regarding where responsibility for carers may lie, pointing to a need for bespoke carer support roles. Some issues may require systemic-level changes. Limitations Findings are from Organisation for Economic Co-operation and Development country English-language publications on adult carers and patients within home care, and carer advisors and stakeholders were based in the United Kingdom, which may limit the transferability of findings. Conclusions Findings provide some clear indicators of factors affecting carer mental health and recommendations. Improvements may require investment in bespoke carer support roles (e.g. carer support nurses) and systemic change (e.g. improving carer identification and assessment, and financial security). Given the enormous contribution carers make to health and social care, they deserve such investment to support them in their work. Funding This synopsis presents independent research funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme as award number 18/01/01. Plain language summary Background Family carers give vital support to people nearing end of life, but their own mental health may suffer as a result. We need to understand what improves or worsens carers’ mental health and tell stakeholders who can make changes for the better. Aim To summarise what we learnt from a review of research and work with carer advisors and other stakeholders, about what can affect carers’ mental health during end-of-life caregiving, and what may help. Method We reviewed research from 2009 to 2019 that looked at factors that may affect carers’ mental health when supporting someone nearing the end of life, worked with a carer Review Advisory Panel (6 members; 9 meetings), and did 6 workshops/discussion groups (36 participants) and a survey (43 participants) with carers/patients, practitioners and policy-makers/commissioners. Results One hundred and six reviewed studies showed the following factors can affect carers’ mental health: (1) how well the patient was doing, (2) how much caregiving affected carers’ lives, (3) how good carer relationships were with the patient and other family, (4) how sufficient their financial resources were, (5) carers’ thoughts, feelings and confidence about caregiving, (6) how good the support was from formal services, family and friends and (7) background: mental health may be better in older carers, worse in females. Carer Review Advisory Panel recommendations included awareness raising, carer ‘road maps’ for guidance, appropriate needs assessment, co-ordinated care through a single contact point, and covering carers’ basic practical and financial needs. Review findings and recommendations made sense to other stakeholders. Improvements may require dedicated carer support workers and systems changes. Conclusions Findings and recommendations give some clear pointers towards improvement, including specific carer support roles and improved financial security. Health and social care make huge savings from carers’ work, and investment should be made to support carers in return. For details and resources: https://arc-gm.nihr.ac.uk/carer-project-. Part of this work was produced by Grande et al.1 under the terms of a commissioning contract issued by the Secretary of State for Health and Social Care. This is an Open Access publication distributed under the terms of the Creative Commons Attribution CC BY 4.0 licence, which permits unrestricted use, distribution, reproduction and adaption in any medium and for any purpose provided that it is properly attributed.